Tempo de amamentação e hábitos de sucção não nutritivos em três grupos de crianças brasileiras - Azevedo, Camilla Moura (2008)
Based on the investigation of 2 to 6-year-old Brazilian children in the complete deciduous dentition phase, divided in three sample groups, that is, white, mulatto or black, and Japanese-Brazilians, this study was developed with the following objectives: 1 - to compare the prevalence of exclusive breastfeeding periods, as well as the prevalence and the mean ages for interruption and persistence of non-nutritive sucking habits (finger sucking and/or pacifier sucking); 2 - to analyze the association between the duration of exclusive breastfeeding with the prevalence of non-nutritive sucking habits. The first group comprised 510 white Brazilian children (265 females and 245 males), the second sample group included 568 mulatto or black Brazilian children (267 females and 301 males), and the third one comprised 405 Japanese-Brazilian children (203 females and 202 males). In order to investigate the breastfeeding duration and the aspects related to finger and pacifier sucking habits, questionnaires were filled out by the parents and/or legal guardians of the children evaluated. The chi-square test (p<0.05) was applied for the assessment of possible differences among the three sample groups, in relation to the duration periods of breast-feeding and also in relation to the prevalence of pacifier and finger-sucking habits. Subsequently, the student “t” test was used to compare the mean ages of interruption and persistence of these non-nutritive sucking habits. Furthermore, the logistic regression model was applied in order to investigate the association between the duration of exclusive breast-feeding and the prevalence of non-nutritive sucking habits, as well as gender differences. Finally, the odds ratio (or) was also calculated for those comparisons that showed statistically significant differences. The results showed that the breastfeeding duration periods were not significantly different between white and mullato or black Brazilian children; however, they were longer for Japanese-Brazilian ones. As far as it concerns the prevalence of pacifier sucking, as well as their mean ages for interruption and persistence, the results did not show significant differences between white and non-white children, but were lower for Japanese-Brazilians. On the other hand, the prevalence of finger sucking habit was greater for females, and also for Japanese-Brazilians, in relation to white and non-white children. However, as far as it concerns the mean ages of interruption and persistence of finger sucking habit, the three groups revealed no significant differences. It was concluded that the prevalence of pacifier sucking habit decreased significantly in children that were breastfed for more than 6 months and, especially, for periods longer that 9 months. In this last group, the risk for developing the above mentioned habit was 7.18 times lower, in relation to children that were never breastfed.